A gyógyítás társadalmi beágyazottsága - Antal Z., László (Szociológiai Szemle, 2024)
The Social background of healing and the elaboration of the integrative forms of healing, presented in the paper, offer such a theoretical framework to research extending over the different fields of healing which is suited to show how seriously the weakening of the social background of healing endangers the health status of the population.I  relied on the categories elaborated by Karl Polányi for the substantive analysis of economic activities when evolving the integrative forms of healing. It is an essential element of Karl Polányi’s logic that self-regulating market is only one possible method of the integration are also given some role in the performance of economic tasks such as households, reciprocity and redistribution, in which the social embedment of economic activity is of different extent. I have constructed the integrative forms of healing along the pattern of the integrative forms elaborated for the analysis of economic processes and then I have applied this conceptual framework to the analysis of the social embedment of healing. This conceptual framework is suited for the analysis of health care within and outside public health in a uniform conceptual framework. In addition, it also offers an opportunity for shedding new light upon the role of state health care played in the society. I was encouraged to elaborate a conceptual framework different from the traditional one when studying the social context of healing, that the analysis of the institutions of health care is often limited to the „state-market'' dispute. Such a broader system of reference allows me to distance myself from this often analysed dimension and to analyse the functioning of the institutions of health care and their role in the totality of healing in a broader context.